Kortárs és ifjúsági: Mark Haddon: A kutya különös esete az éjszakában - Fenyő D., György (Studia Litteraria, 2019)
It is pivotal for contemporary youth literature to be made part of the curriculum, however, it is unnecessary for the education politics to canonise any of them. Contemporary novels give opportunity to discuss important psychological, social, ideological and artistic issues. Within the framework of problem-centred education they prioritise the processed issue besides the aesthetic quality and linguistic accessibility. Mark Haddon’s The Curious Incident of the Dog in the Night-Time provides excellent opportunity to discuss the problems of people with autism and it is also suitable to improve empathy towards them, their families and parents. The study includes a detailed plan for discussion, the questions and exercises are ordered to follow the process of constructive pedagogy: tuning up – creation of meaning – reflection.